Code-Mixing dan Code-Switching dalam Media Sosial: Studi Sosiolinguistik pada Mahasiswa STIE Balikpapan - Ainun Nadiva Salsabila; Angel Deswita Elia Ngasi; Maria Ulfa; Ahmad Jamaluddin; Chandra Malik; Anhar Anhar (Pusat riset dan Inovasi Nasional, 2025)
The digital era has transformed communication patterns among millennials and Gen Z in Indonesia. This study analyzes the phenomenon of code-mixing and code-switching on social media among students at STIE Balikpapan as representatives of the digital generation in a multiethnic environment. Employing a qualitative method with a virtual ethnography approach, data were collected through six months of virtual participant observation and systematic digital documentation across multiple social media platforms. The findings reveal that code-mixing predominantly occurs in intra-sentential and intra-lexical forms, while code-switching takes inter-sentential forms according to communication contexts. The primary factors driving mixed language use are social identity, communication efficiency, and audience adaptation. Balikpapan's multiethnic context enriches these practices through interactions among Indonesian, regional languages, and English. These findings contribute to the field of digital sociolinguistics and serve as a reference for language learning in higher education institutions and the development of Indonesian language policies.